Short‐term changes in polysaccharide utilization mechanisms of marine bacterioplankton during a spring phytoplankton bloom. (16th March 2020) - Reintjes, Greta; Fuchs, Bernhard M.; Scharfe, Mirco; Wiltshire, Karen H.; Amann, Rudolf; Arnosti, Carol
Summary: Spring phytoplankton blooms in temperate environments contribute disproportionately to global marine productivity. Bloom‐derived organic matter, much of it occurring as polysaccharides, fuels biogeochemical cycles driven by interacting autotrophic and heterotrophic communities. We tracked changes in the mode of polysaccharide utilization by heterotrophic bacteria during the course of a diatom‐dominated bloom in the German Bight, North Sea. Polysaccharides can be taken up in a 'selfish' mode, where initial hydrolysis is coupled to transport into the periplasm, such that little to no low‐molecular weight (LMW) products are externally released to the environment. Alternatively, polysaccharides hydrolyzed by cell‐surface attached or free extracellular enzymes (external hydrolysis) yield LMW products available to the wider bacterioplankton community. In the early bloom phase, selfish activity was accompanied by low extracellular hydrolysis rates of a few polysaccharides. As the bloom progressed, selfish uptake increased markedly, and external hydrolysis rates increased, but only for a limited range of substrates. The late bloom phase was characterized by high external hydrolysis rates of a broad range of polysaccharides and reduced selfish uptake of polysaccharides, except for laminarin. Substrate utilization mode is related both to substrate structural complexity and to the bloom‐stage dependent composition of the heterotrophic bacterial community.